Bioceramic synthesis and characterization to be used in major tissue engineering applications [Başlica Doku Mühendisliǧi Uygulamalarinda Kullanilabilecek Biyoseramik Sentezi ve Karakterizasyonu] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2018)
Various disruptions in the body functions resulting from accidents and injuries, reveal the need for biomaterials. Biomaterials are divided into various classes. One of them is bioceramics. Ceramics such as hydroxyapatite (HA), tricalcium phosphate (TCP), which form the inorganic part of the composite, are widely used in biomedical implant applications and bone regeneration due to their bioactive and biodegradable properties. In this study, bioceramic (HA, Florapatite (FA), TCP) synthesis was performed from human tooth minerals. Structural (X-ray Powder Diffraction (XRD), Fouirer Transform Infrared Spektrofotometre (FTIR)) and morphological-elemental (Field Emission Gun Scanning Electron Microscopy (FEGSEM)- Energy dispersive X-ray spectroscopy (EDS)) analyzes of the bioceramic structure have been performed to characterize the materials that can be used in major tissue engineering applications. © 2018 IEEE.
Keywords: Biomaterials; human tooth enamel; hydroxyapatite; synthesis; tissue engineering